2024
DOI: 10.1039/d3cy00809f
|View full text |Cite
|
Sign up to set email alerts
|

A general and expedient amination of alcohols catalysed by a single-site (NN)Co(ii)-bidentate complex under solventless conditions

Rohit Kumar,
Ankit Kumar Srivastava,
Palaniyappan Nagarasu
et al.

Abstract: Here we designed and synthesized a NN–CoII bidentate complex and efficiently used it for general and expedient amination of alcohols under benign, solventless conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
1
0
1
Order By: Relevance
“…8−13 Generally, this reaction involves three steps: dehydrogenation of alcohols to form aldehydes, condensation of aldehydes with amines leading to imines, and hydrogenation of imines to the desired amines, which proceeds by the "transfer hydrogen" or "borrowing hydrogen" mechanism. 14,15 In homogeneous systems, besides noble metal complexes like Ru, 16 Ir, 17,18 etc., the low-cost metal complexes modified by organic ligands, as reported by Beller et al, 19 Balaraman et al, 20,21 and Kempe et al, 22−24 have demonstrated comparable activity and selectivity (Figure 1a). Nevertheless, these catalysts face the challenges including low stability, expensive ligands, residual metals in products, and recovery difficulties.…”
Section: ■ Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…8−13 Generally, this reaction involves three steps: dehydrogenation of alcohols to form aldehydes, condensation of aldehydes with amines leading to imines, and hydrogenation of imines to the desired amines, which proceeds by the "transfer hydrogen" or "borrowing hydrogen" mechanism. 14,15 In homogeneous systems, besides noble metal complexes like Ru, 16 Ir, 17,18 etc., the low-cost metal complexes modified by organic ligands, as reported by Beller et al, 19 Balaraman et al, 20,21 and Kempe et al, 22−24 have demonstrated comparable activity and selectivity (Figure 1a). Nevertheless, these catalysts face the challenges including low stability, expensive ligands, residual metals in products, and recovery difficulties.…”
Section: ■ Introductionsupporting
confidence: 62%
“…Amines and their derivatives are crucial nitrogen-containing organic compounds that play significant roles in various natural products, biologically active molecules, agrochemicals, and pharmaceutical synthesis (Figure d). , Compared with traditional preparation methods (reduction amination, alkylation of ammonia/amines using alkyl halides, reduction of nitriles, etc. ), the N -alkylation of amines with alcohols offers advantages for a green synthesis method for organic amines, including mild conditions, readily available and cost-effective raw materials, and the exclusive generation of water as a byproduct. Generally, this reaction involves three steps: dehydrogenation of alcohols to form aldehydes, condensation of aldehydes with amines leading to imines, and hydrogenation of imines to the desired amines, which proceeds by the “transfer hydrogen” or “borrowing hydrogen” mechanism. , In homogeneous systems, besides noble metal complexes like Ru, Ir, , etc., the low-cost metal complexes modified by organic ligands, as reported by Beller et al, Balaraman et al, , and Kempe et al, have demonstrated comparable activity and selectivity (Figure a). Nevertheless, these catalysts face the challenges including low stability, expensive ligands, residual metals in products, and recovery difficulties.…”
Section: Introductioncontrasting
confidence: 61%